Predictive and Cross-Validation Analysis of Aerobic and Anaerobic Performance Based on Maximum Strength - Alberto Souza Sá Filho; Pedro Augusto Inacio; Vicente Aprigliano; Patricia Sardinha Leonardo; Iransé Oliveira-Silva; Raphael Martins Cunha; Gaspar R. Chiappa; James Oluwagbamigbe Fajemiroye; Rodolfo P. Vieira; Rodrigo Alvaro Brandão Lopes-Martins; Marcelo Magalhães Sales (Applied Sciences)
To establish the capacity of absolute maximum strength and relative to body mass (BM) in deadlift (DL) and squat (SQ) exercises to estimate the maximum anaerobic running performance (MART) and maximum aerobic power (VPeak), among individuals stratified into high (HS) vs. low strength score (LS). The sum of workloads (DL+SQ) was also analyzed and cross-validation was tested. Thirty-four students performed five visits in the first phase. In the first three visits the following were performed: sample characterization and consistency analysis of the maximum repetition (RM) for DL and SQ. Participants were stratified based on DL and SQ relativized by BM (DL/BM and SQ/BM). In the last two visits, MART and VPeak were tested. Linear regression for HS participants did not predict MART for all strength measures. In contrast, the regressive model was significant for DL (R2 = 0.482; p = 0.002), DL/BM (R2 = 0.764; p < 0.001), SQ (R2 = 0.357; p = 0.011) and SQ/BM (R2 = 0.644; p < 0.001) in LS participants, compared to MART performance. For VPeak, linear regression also did not demonstrate an association for all strength measures in HS participants. However, SQ (R2 = 0.309; p = 0.021), DL/BM (R2 = 0.343; p = 0.013) and SQ/BM (R2 = 0.618; p < 0.001) were able to predict VPeak. The prediction from the sum of the DL+SQ produced an association for MART (R2 = 0.451; p = 0.003) and VPeak (R2 = 0.273; p = 0.031) in LS participants. In the second phase of the study, 17 participants performed cross-validation by testing the prediction equations. The same methodological procedures were performed for this phase, but only LS participants were tested. The Wilcoxon test compared real MART vs. predicted for DL (p = 0.02) and SQ (p = 0.043), showing differences, but not for DL/BM (p = 0.051) and SQ/BM (p = 0.093). The Wilcoxon test also showed differences for real VPeak vs. predicted for DL/BM (p = 0.002), SQ (p = 0.019) and SQ/BM (p = 0.05). The MART predictive equation based on DL+SQ did not show differences (p = 0.148), but the same did not occur for VPeak based on DL+SQ (p = 0.008). Maximum strength did not show predictive capacity in HS participants. However, it was significant for LS participants. DL showed greater predictive prominence for MART. In contrast, for VPeak, SQ/BM satisfactorily explained the variations in running performance (61%). The predictive equations of MART by DL/BM and SQ/BM were shown to be accurate, as well as DL+SQ to predict MART.